The effect of elliptical focusing on the threshold of a nanosecond BBO crystal optical parametric oscillator. Issue 21 (15th December 2019) - Rao, C. S.; Kondayya, G.; Kundu, S.; Ray, Alok K.
ABSTRACT: In this paper, we report the results of our numerical model developed to determine the optimum elliptical focusing parameters of the high repetition rate input UV (355 nm) pump beam for achieving reliable low threshold operation of a singly resonant nanosecond β-BaB2 O4 (BBO) based optical parametric oscillator (OPO). The analysis predicts that it is possible to achieve a substantial reduction in the threshold of the OPO by optimizing the 355 nm pump beam in an elliptical focus. We have used our model calculations to find out the maximum size of the elliptical focus for which the threshold pulse energy of the Type-I BBO crystal based OPO is lowered to ∼0.7 mJ. This provides the opportunity for a multi-kHz repetition rate, nanosecond BBO based OPO, pumped with the third harmonic of a DPSSL system operating with a pulse energy of ∼2–3 mJ, while maintaining high average power.